Cardiovascular disease prevalence and prescription patterns at a tertiary level hospital in Bangladesh - Md. Abdul Muhit, Md. Obaidur Rahman, Sheikh Zahir Raihan, Muhammad Asaduzzaman, Mohammad Ahasanul Akbar, Nahid Sharmin, A. B. M. Faroque (Journal of Applied Pharmaceutical Science)
Demographic study of cardiovascular diseases (CVDs) and drug utilization in population is the basis for assessment of cardiovascular disease management. Aim of this study was to analyze the prevalence of CVDs with drug utilization and current trends in Bangladesh. A cross-sectional type of descriptive study was carried out at the outdoor of National Institute of Cardiovascular Diseases (NICVD), Dhaka from July’09 to August’09. A total of 780 patients, who acquiesce with the inclusion and exclusion criteria, were interviewed with structured questionnaire and followed up by prescription monitoring. Out of the total patients with a male, female ratio of 5.3: 4.7, 45.90% patients were over 55 years and 69.62% patients had come from urban area. The patients had lipid level disorder (47.05%), hypertension (28.05%), heart failure (27.25%), ischaemic heart disease (21.55%) and 40.39% were associated with diabetes. Individual patient got 6.35 ± 1.56 no. of drug of different class of which most frequently prescribed drugs were antiatherogenic (97.67%), lipid lowering agents (95.35%), antianginal (79.07%), beta-blockers (51.16%), ACE inhibitors (30.23%), diuretics (37.21%), anxiolytics (81.4%) etc. This data may be propitious for the general physicians for optimizing rational use of cardiovascular drugs and also accessible in formulating strategy for effective cardiovascular disease management.
Keywords: Prevalence,NICVD,prescription,ischemic heart disease